Ten key facts about Future Seeds - Alliance of Bioversity International and CIAT (Bioversity International and the International Center for Tropical Agriculture, 2022)
Ten key facts on Future Seeds, the brand-new genebank of the Alliance of Bioversity International and CIAT in Palmira, Colombia.